Robotics: Science and Systems X 2014
DOI: 10.15607/rss.2014.x.011
|View full text |Cite
|
Sign up to set email alerts
|

Online Trajectory Planning in Dynamic Environments for Surgical Task Automation

Abstract: Abstract-Automation of robotic surgery has the potential to improve the performance of surgeons and the quality of the life of patients. However, the automation of surgical tasks has challenging problems that must be resolved. One such problem is adaptive online trajectory planning based on the state of the surrounding dynamic environment. This study presents a framework for online trajectory planning in a dynamic environment for automatic assistance in robotic surgery. In the proposed system, a demonstration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 18 publications
(27 reference statements)
0
38
0
Order By: Relevance
“…The framework called ProMP models the distribution of the trajectories in the parameter space [10] while the method in [11] modeled the distribution of the demonstrated trajectories at each time step using Gaussian Processes. These studies showed that the demonstrated behaviors can be generalized to new situation by modeling the distribution of the demonstrated trajectories.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The framework called ProMP models the distribution of the trajectories in the parameter space [10] while the method in [11] modeled the distribution of the demonstrated trajectories at each time step using Gaussian Processes. These studies showed that the demonstrated behaviors can be generalized to new situation by modeling the distribution of the demonstrated trajectories.…”
Section: Related Workmentioning
confidence: 99%
“…We assume that the demonstrations are available under various contexts s i . In this case, we can model the conditional distribution of the demonstrated trajectories given the context in order to generalize the demonstrated trajectories to new situations [11], [24], [25]. Here, we use Locally Weighted Regression (LWR) to model this distribution [26], [27].…”
Section: Modelling Demonstrated Trajectory Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Van den Berg et al [34] proposed an iterative technique to learn a reference trajectory and execute it at higher than demonstration speeds for suture knot tying. This work was recently extended by Osa et al [25] to deal with dynamic changes in the environment, but with an industrial manipulator. Mayer et al [20] use principles of fluid dynamics and Schulman et al [31] use non-rigid registration techniques to generalize human demonstrations to similar, yet previously unseen, initial conditions.…”
Section: Related Workmentioning
confidence: 99%
“…These studies include complete automation of time-consuming and repetitive tasks [5], as well as collaborative surgery in which the control is shared back and forth between the operator and the robot [6]. Recent studies have looked into generalizing learned demonstrations to previously unseen initial conditions [7], as well as an adaptive trajectory planning to deal with dynamic changes in the environment [8]. In the field of endovascular intervention these learning-based techniques have been used for automation of motion trajectories from expert demonstrations for the same catheterization task, by a robotic driver, demonstrating potential improvements over manual catheterization [9].…”
Section: Introductionmentioning
confidence: 99%